أهمية التحليل المالي لجدول سيولة الخزينة في تحديد قيمة المؤسسة الإقتصادية - حملاوي, مهدي (جامعة الوادي University of Eloued, 2021)
تهدف هذه الدراسة إلى تسليط الضوء على أهمية التشخيص المالي لجدول سيولة الخزينة، كأداة تعمل على تقديم صورة دقيقة حول تشكل التوازن المالي و كذا مدى تناسق التدفقات النقدية المشكلة له، للتحديد الموضوعي لقيمة المؤسسة الإقتصادية من خلال تحليلنا لجدول سيولة الخزينة لشركة مصنع الآجر برانيس بواسطة مختلف الأدوات التحليلية. خلصت الدراسة إلى أن عملية التشخيص المالي لجدول سيولة الخزينة يحتل مكانة جوهرية في عملية التقييم من خلال ما يوفره من معلومات حول تدفقات الخزينة و التي تقدم نظرة واضحة حول نمو النشاط، تطور الربحية و تسيير احتياجات رأس المال العامل، ما يساهم في التحديد الموضوعي لمجال القيمة و يؤثر عليها بالسلب أو الإيجاب من جهة و التوقع حول مستقبل و آفاق المؤسسة من جهة أخرى. The present study aims to shed light on the importance of the financial diagnosis of the cash flow statement, a tool that provides accurate data of the financial balance and the extent of consistency of the cash flows constituting it, to objectively determine the value of the economic company, we analysed the cash flow statement for “ Branis brick factory”, alongside various analytical tools. The study concluded that the process of financial diagnosis of the cash flow statement plays a vital role in the evaluation process because of the information it provides about cash flows, which in turn provide a clear view on the activity growth, the development of profitability and the management of working capital needs. This contributes in the objective delimitation of the field of value and affects it negatively or positively and anticipating the future and prospects of the institution
The importance of the financial analysis of the cash flow statement on determining the value ofthe economic company Case Study of “Branis brick factory”
مقال
Keywords: قيمة المؤسسة ; التحليل المالي ; جدول سيولة الخزينة ; التوازن المالي